Postoperative pain in abdominal surgery: A review of strategies to optimize management and minimize the use of opioids (Research, Society and Development, 2024)
The objective of the present article was to evaluate the effectiveness of post-operative pain management techniques, minimize the use of opioids, and know the respective complications of such drugs. A systematic literature review was carried out by searching the Pubmed, Lilacs, and Scielo databases, using standardized descriptors “Postoperative pain” “Pain control” and “non-opioid analgesics”, in English, and after selecting articles relevant to the study, 15 articles were reviewed. Results: The drugs, Nefopam, Parecoxib, and Ibuprofen, reduced post-operative pain and opioid use. The infusion of ropivacaine and methylprednisolone into the wound was effective but did not reduce opioid consumption. Among the blockades, the choice of an ideal blockade applied to each type of surgery shows good results. The most common medication in clinical trials was morphine (33%), and they also used standardized scales to assess postoperative pain scores, namely VAS and NRS. In addition to efficacy in minimizing opioids, some studies evaluated secondary outcomes, such as urinary retention, return to oral intake, mobilization in bed, and reduction of interleukins. However, a study focused on non-opioid techniques for a single type of surgery, separating laparoscopic and open, would have greater validity.